The Antecedents of Value Creation in Singapore Corporation - Tan, Wee Liang (Institutional Knowledge at Singapore Management University, 2004)
The impetus for value creation has led to greater interest in encouraging entrepreneurship within organizations (intrapreneurship). The intrapreneurship literature reveals general agreement that organizational entrepreneurship flourishes where the environmental conditions of an organization are most favorable. However, there is little empirical research examining the relationship of the organizational climate and the intentions of employees to be intrapreneurs, and their actual participation in such activities. This paper reports a study on the elements of organizational climate on intrapreneurship attitudes, intentions and actions on the part of middle managers in corporations in Singapore.